Fluid Flow Through Serieal Parallel Circular Cylinder Arranged In Tandem - Nur Ikhsani; Nasaruddin Salam; Luther Sule (EPI International Journal of Engineering, 2021)
The Fluid flow through circular cylinders in serieal parallel positions arranged in tandem were analyzed computationally and experimentally at nine levels of Reynolds number, ReD 34,229; 47,921; 61,612; 75,304; 88,996; 102,688; 116,379; 130.071 and 143,763 The variation in the ratio of the distance between the front and rear cylinders is determined as M / D = 0.3, M / D = 0.5, M / D = 0.7, M / D = 0.9, and M / D = 1.1. While the distance between cylinder number 2 and 3 we set constantly and determined as N / D = 5 cm. The results displayed are flow velocity with computational approach validated by flow visualization, computational pressure contour, and drag coefficient through experimental testing. The results showed that the smallest boundary layer thickness was obtained in the model with a distance ratio of M / D = 2.5, using both computational and experimental approaches. The characteristics of the minimum pressure contour and the lowest drag coefficient (CD) = 0.7572 were also obtained at the ratio of the distance M / D = 0.25 and at upstream speed of 21 m / s